Cohort-friendly protocol for a sensitive and fast method for trihalomethanes in urine using gas chromatography—Triple quadrupole mass spectrometry - Charisiadis, Pantelis; Makris, Konstantinos C. (My University, 2018)
A cohort-friendly biomonitoring protocol has been developed for measuring biomarkers of exposure to disinfection by-products (trihalomethanes, THM) in urine using small initial volume (3 mL) and short analysis time (∼10 min) that facilitates the throughput of a large number of samples. The objective of this study was to optimise a cohort-friendly biomonitoring protocol for the determination of four THM analytes in human urine using gas chromatography coupled with triple quadrupole mass spectrometry (GC-QqQ-MS/MS). The proposed methodology will facilitate the inclusion of such urinary THM measurements into large population health studies.
Keywords: Biobanks; Biomarkers; Chlorine; Cohorts; Disinfection by products; Exposure